PENUMBUHAN DAN KARAKTERISASI LAPISAN TIPIS PbTiO3 YANG DISIAPKAN DENGAN TEKNIK SPIN COATING - Bilalodin Bilalodin (Universitas Jenderal Soedirman, 2008)
The growth of PbTiO3 ferroelectric thin films have successfully done. Thin films were made from bulk (powder) PbTiO3 dissolved in methanol solution. The condensation was mixed during 1 hour to get homogeneous condensation. Thin films were grown above corning substrates by spin coating method. Optimation was done by various of annealing temperature. The physical properties of thin films were characterized by Energi Dispersive X-Ray Spectroscopy (EDS), X-Ray Diffraction (XRD), Scanning and Electron Microscopy (SEM). EDS measurement showed that the stoichiometry composition ratio of Pb/Ti is 1/1.26 at annealing temperature 600oC and 1/1.29 at annealing temperature 700oC. The result of XRD pattern showed that crystal structure of PbTiO3 thin films are tetragonal. The calculated lattice parameters ontained from Chohen Method are a=b= 3.873 Å dan c= 4.130Å. The result of SEM PbTiO3 thin film showed that thin film has globular grain size.